Bioactive Algae in Wound Healing: Natural Solutions for Modern Medicine - Ashwini A. Aher; Sunil N. Thitame; Mopagar Viddyasagar; Anil S. Wabale (Journal of Pharmacy and Bioallied Sciences)
The increased focus on green and environmentally friendly approaches to wound healing has prompted consideration of marine resources as a source of bioactive agents: in particular, algae contain a variety of compounds. The purpose of this paper concerns the versatile function and characteristics of algae, which includes anti-inflammatory properties, antibacterial activity, and a variety of other characteristics. Algae products have water-retaining and biocompatibility properties that enable the growth of body cells and new tissues without the formation of scars and contracting skin. This paper looks at the possibility of algae being used as a basis for new wound care formulations in the form of hydrogels and topical formulations. Finally, using algae’s features in wound healing treatments is one of the ideas of combining biological and medical innovation to create safer and more eco-friendly medicines for patients.